Restauração florestal no Brasil: avaliação produtiva e mercado pós acordo de Paris - Grandini, Guillermo Antonio Cerávolo (Universidade Federal de São Carlos, 2024)
The present study seeks to assess the productive capacity of seedlings and seeds in Brazil, identifying the main actors in the reforestation market and the associated challenges, in the context of the goals established by the Paris Agreement. The methodology employed involves literature review and quantitative analysis, aiming to detail the role of the companies involved and the dynamics of this market. The results showed a notable growth of the sector after the Paris Agreement, highlighting the consultancy services and the generation and commercialization of carbon credits. However, currently, without considering the country's natural regeneration, the production of seedlings and seeds is insufficient to meet the reforestation target of 12 million hectares committed at COP21. The contributions of this work are significant for the decision-making by companies, investors, research institutions, and public policy makers, providing a knowledge base that can guide initiatives to achieve environmental sustainability goals and position Brazil as a leader in low greenhouse gas emissions. The discussion emphasizes the need for expansion and improvements in the seedling production segment, both in terms of quantity, with the construction of more nurseries, and quality, through the development of new technologies, reproduction protocols, and the development of new public policies that facilitate this process. The conclusions point to the urgency of strategies addressing the gap in production and the lack of skilled labor, proposing measures for the training of professionals and the encouragement of reforestation project execution.
Forest restoration in Brazil: productive assessment and market post-Paris agreement
Keywords: Produção de mudas nativas; Crédito de carbono; Desmatamento; Mudanças climáticas; Native seedling production; Carbon credit; Deforestation; Climate change; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS::ECONOMIA AGRARIA